Relapsing Neurological Complications in a Child With ATP1A3 Gene Mutation and Influenza Infection: A Case Report - Pisapia, Raffaella; Capoluongo, Nicolina; Palmiero, Giulia; Tascini, Carlo; Rescigno, Carolina (Frontiers in Neurology, 2021)
Abstract Mutations in the ATP1A3 gene, encoding the α3 subunit of Na+/K+-ATPase, are associated to different neurological manifestations, that may be elicited by febrile episodes. A recently described phenotype, linked to the p.Arg756Cys mutation, is clinically characterized by Relapsing Encephalopathy with Cerebellar Ataxia (RECA). In our case, a diagnosis of RECA has been established, despite an alternative, reasonable cause had been already identified. We describe the case of a child with two recurrent episodes, two years apart, of hypotonia and ataxia. In both episodes, a laboratory-confirmed influenza virus infection suggested the diagnosis of influenza-associated encephalopathy. After the second episode, a search for genetic mutations was performed, and ATP1A3 mutation, associated to RECA, was found. After both episodes, the child was discharged after partial improvement of neurological conditions. The diagnosis of encephalopathy in children is often challenging. A genetic predisposition to neurological decompensation should be suspected in case of recurrent episodes, even if an alternative diagnosis has been established. Indeed, febrile infections may represent only the trigger of neurological involvement. In these patients, the knowledge of a genetic predisposing factors may help in the prevention of neurological episodes, by the promptly use of anti-pyrectics and preventive measures as appropriate vaccination.